How can additive manufacturing enhance supply chain resilience: a potential framework and operational strategies - Shih, Chun-Hsun (2021)
Additive manufacturing (AM), well-known as 3D printing, is an ongoing trend in various industries. The technology enables greater freedom of product design which challenges conventional production methods with its great potential to push forward geometric design and boundary limits. Besides revolutionising the concept of product design, the technology jointly has different degree of impacts on activities within the entire process of supply chain (SC) planning and operations. Since the outbreak of coronavirus pandemic (COVID-19) in the early beginning of 2020, the world has been experiencing its unprecedented, turbulent times ever. A great range of industries have been encountering challenges which are never seen and expected. Lots of companies were forced to react to the disruption abruptly.